Long‐term outcomes following surgical repair of coronary artery fistula in adults. Issue 12 (7th October 2021) - Wada, Yuki; Marui, Akira; Arai, Yoshio; Nagasawa, Atsushi; Tsumaru, Shinichi; Arakaki, Ryoko; Iida, Jun; Kuroda, Yuki; Tamai, Yumeka; Fukushima, Takashi; Soga, Yoshiharu
Abstract: Background and Aim of the Study: Coronary artery fistula (CAF) is a relatively rare cardiac anomaly. We investigated long‐term outcomes following surgical repair of CAF in adults. Methods: We retrospectively investigated 13 consecutive patients undergoing surgical repair of CAF in our institution between 2008 and 2019 (67.3 ± 10.4 years old, 38% male). CAF types were coronary artery‐pulmonary artery fistula (77%), coronary artery‐coronary sinus fistula (15%), and both (8%). CAFs originated from the left coronary artery (38%), right coronary artery (8%), and bilateral coronary arteries (38%). Pulmonary and systemic flow (Qp/Qs) was measured in seven patients (54%), with a mean value of 1.52. Seven patients underwent surgery for CAFs alone, and others simultaneously underwent surgery for comorbid cardiac diseases. Results: All procedures were conducted under cardiopulmonary bypass. Surgical procedures were direct epicardial ligation of fistula (92%), direct closure of CAF through pulmonary artery incision (38%), direct closure of CAF through coronary sinus incision (8%), or patch closure of CAF through coronary artery incision (8%). Myocardial perfusion scintigraphy showed asymptomatic myocardial ischemia in the right coronary area after surgery in one patient. There were no deaths perioperatively or during follow‐up (mean: 66.6 months). There were no coronary or other CAF‐related events. Conclusions: Several anatomical variations in CAF were observed which coexist with cardiac disease. Long‐term outcomes following surgical repair were satisfactory, and the concurrent intervention of CAFs during surgery for comorbid cardiac disease is useful to prevent future complications related CAFs in adults.